Studi Kasus: Pengaruh Rendam Kaki Air Hangat Dan Jahe Merah Pada Keluarga Dengan Hipertensi - Peni Sila Arsita Dewi, Peni; Wardah , Wardah; M. Zul’Irfan, M. Zul’Irfan; Hendra, Donny (Jurnal Keperawatan Komplementer Holistic, 2025)
Hypertension is a global health problem with a prevalence of 22% globally and requires serious attention. The successful management of hypertension depends not only on medical intervention, but also on the active role of the family in health maintenance. Lack of family involvement can lead to patient non-compliance with medication and a healthy lifestyle. This study aims to measure the effectiveness of warm water and red ginger foot bath therapy on blood pressure reduction and assess the role of family in maintaining the health of hypertensive patients. The study was conducted in Sungai Putih Village, Tapung District, Kampar Regency in May 2025 with a pre-test and post-test design. Analysis using frequency distribution on two subjects. The results showed a significant increase in family health maintenance based on the Indonesian Nursing Outcome Standards. Adaptive behavior increased from a score of 3 to 5, understanding of healthy behavior from 2 to 5, ability to carry out healthy behavior from 2 to 5, help-seeking behavior from 1 to 5, interest in improving healthy behavior from 3 to 5, and support system from 2 to 5. These results indicate that the combination therapy of warm water foot bath and red ginger is effective in increasing family involvement and health maintenance of patients with hypertension. This intervention is recommended as a supporting therapy that can be applied routinely in the family environment.